The Transcallosal Anterior Interfoniceal Approach: A Microsurgical Anatomy Study - Graziano, F.; Ganau, M.; Meccio, F.; Iacopino, D. G.; Ulm, A. J. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objectives A plethora of surgical strategies have been described to reach deep-seated lesions situated within the third ventricle including the Rosenfeld, or transcallosal anterior interfoniceal (TAIF), approach. First introduced in 2001, it consists of a small callosotomy followed by the midline transseptal dissection of fornices to enter the roof of the third ventricle. The aim of this microsurgical anatomy study is to describe and show each stage of the surgical procedure, focusing on the possible trajectories to anatomical landmarks.Participants A total of 20 adult cadaveric specimens were used in this study. Using ×3 to ×40 magnifications, the surgical dissection was performed in a stepwise fashion, and the transcallosal anterior interforniceal approach was performed, analyzed, and described.Results In 5 specimens of 10, a cavum septum pellucidum was depicted. In 5 cases of 20 after the callosotomy ,the lateral ventricular cavities were reached. Different orientation of the microscope allowed us to define three surgical trajectories to visualize the region of interest without exposing important functional areas.Conclusion The TAIF represents a minimally invasive approach to the third ventricle; its tricky surgical steps make appropriate anatomical dissection training essential to become confident and skilled in performing this approach.
Keywords: microsurgical anatomy; third ventricle; transcallosal anterior interfoniceal approach